The Cooperative Effect of In2O2 and In/HZSM-5 for Reduction of Nitric Oxide with Methane - Lili Ren (Journal of Chemistry)
Compared with In/HZSM-5 catalyst, In/HZSM-5/In2O3 catalyst that contained two different kinds of In induced by the impregnation and the physical mixing method, respectively, has shown remarkable activity for methane selectively catalytic reduction (CH4-SCR) of NOx. The addition of In2O3 to In/HZSM-5 could improve the NO conversion. When a little In2O3 was added to the In/HZSM-5, the active sites of InO+ which can adsorb NO2 were increased. Moreover, at the internal surface of HZSM-5, highly dispersed In2O3 species could promote oxidation of NO to NO2. The adsorption of NO2 is the key step for the whole reaction, which benefits the activation of methane and the reduction of NOx by methane. Thus the activity of In/HZSM-5/In2O3 for CH4-SCR of NOx was higher than that of In/HZSM-5.